2015
DOI: 10.1002/cne.23935
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional immersive virtual reality for studying cellular compartments in 3D models from EM preparations of neural tissues

Abstract: Advances in the application of electron microscopy (EM) to serial imaging are opening doors to new ways of analyzing cellular structure. New and improved algorithms and workflows for manual and semiautomated segmentation allow us to observe the spatial arrangement of the smallest cellular features with unprecedented detail in full three‐dimensions. From larger samples, higher complexity models can be generated; however, they pose new challenges to data management and analysis. Here we review some currently ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…Accordingly, electron microscopy studies of brain sections described predominant glycogen localization to be in astrocytic peri‐synaptic microprocesses and endfeet (Cataldo & Broadwell, ; Maxwell & Kruger, ) and in pericytes to a smaller extent (Cataldo & Broadwell, ). Moreover, a recent study using a modern automated serial microscope achieved three‐dimensional reconstruction of neuropil and quantitated preferential localization of glycogen particles in perisynaptic processes and endfeet (Calì et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, electron microscopy studies of brain sections described predominant glycogen localization to be in astrocytic peri‐synaptic microprocesses and endfeet (Cataldo & Broadwell, ; Maxwell & Kruger, ) and in pericytes to a smaller extent (Cataldo & Broadwell, ). Moreover, a recent study using a modern automated serial microscope achieved three‐dimensional reconstruction of neuropil and quantitated preferential localization of glycogen particles in perisynaptic processes and endfeet (Calì et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of glycogen granules initially appeared to have a random distribution, but they were discovered to be grouped into clusters of various sizes with particular spatial relationships to specific tissue features. The authors found the immersive evaluation of the 3D structure to be pivotal to identify such non-random distribution (Cali et al, 2015). The use of an interactive VR room also allowed multiple users to share and discuss the evaluation of the cellular details.…”
Section: Scientific and Data Visualizationmentioning
confidence: 99%
“…Moving from the nanoscale to the microscale, a specific task consisting of the evaluation of the spatial distribution of glycogen granules in astrocytes (glial cells, a type of brain cells) was evaluated in an immersive environment in a Cave-like system (Cali et al, 2015). A section of the hippocampus of 226 μm 3 at a voxel resolution of 6 nm was 3D reconstructed based on electron microscopy image stacks.…”
Section: Scientific and Data Visualizationmentioning
confidence: 99%
“…Although neurons are thought to be the primary energy consuming cells in brain, astrocytes contain the vast majority of brain glycogen. Electron microscopy identified glycogen granules throughout astrocyte cell bodies and processes, particularly near axonal boutons and dendritic spines (Cali et al, ). Glutamate uptake is an energy‐intensive astrocyte function and interestingly glycogen phosphorylase has been found to be associated with the astrocyte glutamate transporter, GLT‐1 (Genda et al, ).…”
Section: Brain‐specific Aspects Of Glycogenmentioning
confidence: 99%
“…Glycogen levels found in adult rat under physiological conditions are as follows: liver >> skeletal muscle > cardiac muscle > brain > kidney (Table ). Glycogen in the mammalian brain is localized primarily to astrocytes, but much smaller amounts are also found in meningeal cells, endothelial cells, and other cell types (Calì et al, ; Cataldo & Broadwell, ; Koizumi, ; Wender et al, ). Neurons contain appreciable amounts of glycogen during development, but this falls to very low levels in the mature brain except in certain brainstem neurons (Borke & Nau, ; Cataldo & Broadwell, ; Cavalcante, Barradas, & Vieira, ; Ibrahim, ; Koizumi, ; Oe, Baba, Ashida, Nakamura, & Hirase, ; Saez et al, ).…”
Section: Introductionmentioning
confidence: 99%